2009
DOI: 10.1039/b908392h
|View full text |Cite
|
Sign up to set email alerts
|

FtmOx1, a non-heme Fe(ii) and α-ketoglutarate-dependent dioxygenase, catalyses the endoperoxide formation of verruculogen in Aspergillus fumigatus

Abstract: Verruculogen is a tremorgenic mycotoxin and contains an endoperoxide bond. In this study, we describe the cloning, overexpression and purification of a non-heme Fe(ii) and alpha-ketoglutarate-dependent dioxygenase FtmOx1 from Aspergillus fumigatus, which catalyses the conversion of fumitremorgin B to verruculogen by inserting an endoperoxide bond between two prenyl moieties. Incubation with (18)O(2)-enriched atmosphere demonstrated that both oxygen atoms of the endoperoxide bond are derived from one molecule o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 31 publications
2
109
0
2
Order By: Relevance
“…Using recombinant enzymes, we have demonstrated that FtmPT2/FtmH catalyzes the prenylation of 12,13-dihydroxyfumitremorgin C in the presence of dimethylallyl diphosphate, resulting in the formation of fumitremorgin B, 35 which is then converted to verruculogen by FtmOx1/FtmF by inserting an endoperoxide bond between the two prenyl moieties. 32 We have shown that FtmOx1 reaction was absolutely dependent on the presence of Fe(II) and a-ketoglutarate, and therefore functions as a non-heme Fe(II) and a-ketoglutaratedependent dioxygenase. Known a-ketoglutarate-dependent dioxygenases usually transfer one oxygen atom to the substrate and another to a-ketoglutarate resulting in the formation of succinate.…”
Section: Molecular Biological and Biochemical Investigations On The Bmentioning
confidence: 91%
See 3 more Smart Citations
“…Using recombinant enzymes, we have demonstrated that FtmPT2/FtmH catalyzes the prenylation of 12,13-dihydroxyfumitremorgin C in the presence of dimethylallyl diphosphate, resulting in the formation of fumitremorgin B, 35 which is then converted to verruculogen by FtmOx1/FtmF by inserting an endoperoxide bond between the two prenyl moieties. 32 We have shown that FtmOx1 reaction was absolutely dependent on the presence of Fe(II) and a-ketoglutarate, and therefore functions as a non-heme Fe(II) and a-ketoglutaratedependent dioxygenase. Known a-ketoglutarate-dependent dioxygenases usually transfer one oxygen atom to the substrate and another to a-ketoglutarate resulting in the formation of succinate.…”
Section: Molecular Biological and Biochemical Investigations On The Bmentioning
confidence: 91%
“…36 In contrast, both oxygen atoms from a single O 2 molecule were incorporated into the structure of verruculogen, which was proven by incubation of fumitremorgin B with FtmOx1 in 18 O 2 enriched atmosphere. 32 Therefore, FtmOx1 represents the first endoperoxide forming non-heme Fe(II) and a-ketoglutarate-dependent dioxygenase reported so far. Until now, functions of two genes ftmMT/ftmD and ftmO/ftmI have to be proven experimentally.…”
Section: Molecular Biological and Biochemical Investigations On The Bmentioning
confidence: 97%
See 2 more Smart Citations
“…The stereoselective synthesis of deuterated analogues of Lglutamate was accomplished by Schofield and the analogues used in a study on carbapenem biosynthesis ( Figure 6B) (Ducho et al, 2009). A report on the first -ketoglutarate-dependant dioxygenase with non-heme Fe(II) to catalyse the formation of an endoperoxide bond has appeared (Steffan et al, 2009). This enzyme was shown to convert fumitremorgin B to verruculogen by the insertion of an endoperoxide bond using both oxygen atoms of O 2 .…”
Section: Natural Products -Isolation Synthesis and Biosynthesismentioning
confidence: 99%